Microbiological Profile in Oral Cavity Infection in Diabetic Rats with Periodontitis - Ermawati, Tantin; Indriana, Tecky; Hamzah, Zahreni; Suhartini, Suhartini; Rachmawati, Dessy (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Diabetes melitus is a chronic metabolic disease due to the inability of the pancreas to produce insulin or the body cannot use insulin effectively.Periodontitis is one of the complications of microvascular disorders that ranks second in oral cavity diseases. One of the aerobic bacteria thought to play a role in the severity of diabetes melitus is Staphylococcus aureus, while the pathogenic anaerobic bacteria in periodontal disease are Treponema, Bacteroides, Porphyromonas, Prevotella, Capnocytophaga, Peptostreptococcus, Fusobacterium, Actinobacillus, and Eikenella. The study aimed to determine the microbiological profile in oral cavity infections of rats with diabetes melitus and periodontitisMethod: This study was experimental laboratories on male wistar rats induced by diabetes melitus and periodontitis using wire ligature on mandibular molars, which were divided into 3 treatment groups: group I (control), group II (diabetes melitus) and group III (diabetes melitus and periodontitis). Periodontitis (wire) rats were treated for 7 days and saliva was collected to identify the microbiological profile of the oral cavity. Result: Identification indicated the presence of genus and species of bacteria in the saliva of rats in 3 groups, gram positive: Staphylococcus intermedius, Staphylococcus cohnii subsp.urelyticus. Gram negative: Chromobacterium violaceum, Kleibseilla pneumoniae, Eikenella corrodens, Enterobacter sakazaki and Chryseobacterium meningosepticum. Conclusion: The number of bacterial colonies in the treatment group of diabetes melitus and periodontitis rats was greater than the treatment group of diabetes melitus rats and the control group. Gram staining results found groups of gram positive and gram negative bacteria.